Пожалуйста решите !)!) Преобразуйте в многочлен выражение: 1... 7c(4c+2)-(7+c)^2 2... -3c(6c+2)-(-3+c)^2 3... 6c(9c+2)-(6+c)^2
Пожалуйста решите !)!)
Преобразуйте в многочлен выражение:
1... 7c(4c+2)-(7+c)^2
2... -3c(6c+2)-(-3+c)^2
3... 6c(9c+2)-(6+c)^2
Ответ(ы) на вопрос:
1...=28c²+14c-49-14c-c²=27c²-49.
2...=-18c²-6c-(c-3)²=-18c²-6c-c²+6c-9=-19c²-9.
3...=54c²+12c-36-12c-c²=53c²-36.
1) =28с²+14с-49-14с-с²=27с²-49
2) =-18с²-6с-9+6с-с²=-19с²-9
3) =54с²+12с-36-12с-с²=53с²-36с
Не нашли ответ?
Похожие вопросы